Vernadsky G. (translated by): Medieval Russian Laws - Koranyi, Karol (Czasopismo Prawno-Historyczne, 1949)
Recenzja: Medieval Russian Laws. Translated by G e o r g e V e r -n a d s y (Number XLI of the Records of Civilisation Sources und Studies. Austin P. Evans Editor), New York 1947, Columbia University Press, s. 106. [Wyjaśnienie, Zygmunt Lisowski ... 501-502]